Near-field optical trapping with an actively locked cavity - van Leeuwen, N; Moore, L; Partridge, W; Peverall, R; Ritchie, G; Summers, MD (2011)
This paper details the construction and performance of a resonant cavity evanescent wave trap for the trapping and assembling of microparticles. The technique employs a low finesse resonator which incorporates total internal reflection (TIR) at the silica/water interface to generate an evanescent field which is coherently scattered by silica microparticles present in suspension to form optically bound structures. Circulating powers of 14W over an area of 150νm × 75νm were generated with a 400mW Nd:YAG source. This approach allows some degree of control over the shape of the evanescent field by locking to higher-order cavity modes. © 2011 IOP Publishing Ltd.